Antioxidative capacity of crude camellia seed oil: Impact of lipophilization products of blueberry anthocyanin. (29th December 2017) - Luo, Shui-Zhong; Chen, Sa-Sa; Pan, Li-Hua; Qin, Xin-Sheng; Zheng, Zhi; Zhao, Yan-Yan; Pang, Min; Jiang, Shao-Tong
ABSTRACT: Natural antioxidants have received considerable research interest nowadays, especially their usage in oil products. Blueberry anthocyanin extracts were added to crude camellia seed oil and lipophilized with free fatty acids in the oil through enzymatic process. The results showed that lipophilized anthocyanin derivates were synthesized, the oxidative stability of the oil under high temperature was improved, and the content of free fatty acids of the crude camellia seed oil was decreased. In conclusion, enzymatic lipophilization of blueberry extracts with free fatty acids in crude camellia seed oil could improve the quality of oil, especially the performance under high temperature.